Chemical constituents of Curcuma Heyneana and Curcuma Zedoaria - Mohd. Yusoff, Nurul Zulaikha (2017)
Curcuma zedoaria and C. heyneana are two species belong to the Zingiberaceae family. The essential oils and phytochemical of these two species have been studied. The essential oils of the fresh rhizomes of C. zedoaria and C. heyneana were extracted by using the hydrodistillation technique and analysed by gas chromatography and gas chromatography–mass spectrometry (GC-MS). Hydrodistillation of C. zedoaria gave 71.3% while C. heyneana yielded 63.6% of essential oils comprised of monoterpenes, sesquiterpenes, oxygenated monoterpenes, and oxygenated sesquiterpenes. The major component presence in C. zedoaria was furanogermenone (42.2%), while in C. heyneana were ar-turmerone (13.9%) and germacrone (14.4%). Extraction of dried rhizomes of both Curcuma species was done by soxhlet extraction method using chloroform. Fractionation and purification using vacuum liquid chromatography (VLC) and preparative thin layer chromatography (PTLC) successfully isolated ar-turmerone, curcumin and a-turmerone from C. heyneana while furanogermenone and isofuranodiene were obtained from C. zedoaria. Their structures were elucidated by spectroscopic method such as IR, 1H NMR and 13C NMR spectroscopies. The antioxidant activity of essential oils and crude extracts were carried out using 2,2-diphenyl-1-picrylhydrazyl radical (DPPH), 2,2?-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS), and ferric reducing antioxidant power (FRAP) assay. The antioxidant screenings revealed that crude extract of C. heyneana had strong antioxidant radical scavenging with DPPH assay (IC50 50.93 µg/mL), ABTS (IC50 90.90 µg/mL) and FRAP (85.70 mM).